Pengaruh Takaran Pupuk Organik Fermentasi (Porasi) Ampas Aren Dengan Kotoran Ayam Terhadap Pertumbuhan dan Hasil Cabai Merah (Capsicum Annuum L.) - Priyadi, Rudi; Juhaeni, Ade Hilman; Haryadi, Fauzi Isma (Universitas Musamus, Merauke, Papua, 2021)
One of the efforts that can be made to increase the yield of red chili plants is by providing nutrients, one of which is the supply of organic fertilizers such as poration. Poration is fermented organic matter using bioactivators / bio-fertilizers M-Bio which functions to fertilize the soil and increase plant growth and yield. The purpose of this study was to obtain the best poration dose for palm waste and chicken manure for growth and yield of red chilies. This research was conducted from July to December 2020, at the Experimental Garden of the Faculty of Agriculture, Siliwangi University, Mugarsari Village, Tamansari District, Tasikmalaya City with an altitude of 374 meters above sea level. This research was conducted with an experimental method using a randomized block design (RBD) consisting of 6 treatments and 4 repetitions. The results of this study indicate that the measurement of poration of palm waste and chicken manure has an effect on the growth and yield of chili plants (Capsicum annuum L.).